The impact of psychological capital on employees' organizational commitment - Huong, Nguyen Thuy; Trung, Nguyen Tan; Phuong, Ha Thi Thu; Hieu, Vu Dinh; Phuong, Mai Quynh (Edelweiss Applied Science and Technology, 2025)
An organization's core value is its people, and since it influences the business success of the company, employee organizational commitment is crucial to raising the caliber of human resources. In the disciplines of sociology and management, psychological capital is now one of the most studied subjects. Anyone with positive psychological capital will undoubtedly have an advantage in any field. The purpose of this research is to learn, evaluate, and measure the impact of psychological capital on the organizational commitment of employees in firms. The authors use a qualitative research method with document review techniques, including previous studies, expert interviews, comparison, synthesis, and analysis. The quantitative research method is carried out with the support of SPSS software. Techniques of quantitative research include analyzing the reliability of the scale through the Cronbach's alpha coefficient, EFA analysis, and model regression testing. The results show that psychological capital, including confidence, hope, optimism, and resilience, has a positive influence on employee organizational commitment. We offer some suggestions for businesses and workers on psychological capital to increase employees' organizational commitment based on the study's findings.